Strategic timing of entry: Evidence from video games - Benjamin Engelstätter; Michael R. Ward (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper investigates how video game publishers' choice of game release date is affected by the expected level of competition within the game's product niche. We identify game niches by genre, age-appropriateness, a four week window cohort, publisher and console system. Our analysis is based on two different video game data sets, one based on industry sales data and the other featuring extensive consumer usage information. We show that consumer substitution across games is stronger within most of the dimensions describing product niches. Sales volumes decay quickly after the opening weekend, so at any point in time, a niche willtypically be served by few current titles. Thus, publishers have incentives to avoid releasing during periods of fierce intra-niche competition. We show that games are more likely to be released so as to avoid weeks when their niche is relatively well served.
urn:nbn:de:bsz:180-madoc-353911
Keywords: D43; L13; L96; 330; Product Entry; Non-Price Competition; Niche; Strategy; Submarkets; Entertainment Goods; Video Games